Exploring the connection: Personality traits and performance expectancy in online training for science teachers - Shan Cao; Naveed Saif; Abdullah Muzil Alharbi; Mona Muzil Alharbi; Irfan Ullah Khan (Acta Psychologica, 2025)
This study investigates the relationships between personality traits and performance expectancy (PE) in online learning environments, focusing on the Big Five personality dimensions. For this purpose data was obtained from science teachers of government schools in developing country (Pakistan) prospective. Data was analyzed through SEM approach via measurement and structural model analysis. Results indicate that perceived agreeableness and Conscientiousness had positive, significant effects on PE indicating that self-generated performance expectations are higher among people with high levels of (AGRE) and (CON). A similar but less significant correlation of extraversion with performance expectancy was observed. On the other hand, there was also significant path relationship between Openness to Experience and performance expectancy but in inverse direction, that indicate people with many interests may have a problem being expected to excel in certain domains. More importantly, the influence of Neuroticism on performance expectancy is insignificant indicating that this attribute of trainee's personality traits and learning outcomes is not supported in the current study. These findings add to knowledge in education and related fields by emphasizing the relevance of personality and ideas that practitioners and other stakeholders in learning organizations can use to develop positive learning experiences. With regard to suggestions for future research, it is suggested to take into account the contextual cues, follow the longitudinal perspective, and consider other models of personality to gain better insights into these processes.